2014
DOI: 10.1583/13-4588mr.1
|View full text |Cite
|
Sign up to set email alerts
|

Histological Observations One Year After Mechanochemical Endovenous Ablation of the Great Saphenous Vein

Abstract: MOCA is a novel endovenous treatment modality for saphenous vein insufficiency. Results of MOCA on the cellular level are essential to optimize treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…A total of 28% of patients presented with small hematomas, 17% had local skin hardening, and 18% felt discomfort for more than a week after the procedure. High effectiveness of this method over follow-up periods ranging from 6 to 24 months has been confirmed in several other studies [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 59%
“…A total of 28% of patients presented with small hematomas, 17% had local skin hardening, and 18% felt discomfort for more than a week after the procedure. High effectiveness of this method over follow-up periods ranging from 6 to 24 months has been confirmed in several other studies [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 59%
“…One of MOCA device is ClariVein (Merit Medical, South Jordan, Utah) that combines mechanical injury to the venous endothelium using a rotating wire with simultaneous delivery and dispersion of a liquid sclerosant [5]. The liquid sclerosant causes irreversible damage to the cellular membranes of the endothelium, resulting in the fibrosis of veins [6]. Another technique to produce a nontumescent sclerosantassisted ablation is by means of Flebogrif (Balton, Poland), a device that is scratching the endothelium lining by a dedicated catheter.…”
Section: Introductionmentioning
confidence: 99%
“…These together lead to occlusion of the vein. 39 The procedure is associated with faster recovery and less post-procedure pain and discomfort. 40 The procedure has several advantages over other ablative techniques, including (a) reduced pain, bruising and discomfort, (b) no tumescent anesthesia, (c) no risk of nerve and skin damage, and (d) rapid return to regular activity.…”
Section: Mechanochemical Endovenous Ablationmentioning
confidence: 99%
“…42 MOCA has shown a closure rate of 87 to 96%. 39,43 A randomized controlled trial comparing MOCA and RFA showed a closure rate of 92% at 4 weeks. 44 Tang et al reported no difference in occlusion while treating GSV and SSV.…”
Section: Mechanochemical Endovenous Ablationmentioning
confidence: 99%